DINAMIKA UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK PERLINDUNGAN HUKUM DAN ANCAMAN KEBEBASAN BEREKSPRESI - Lutfi Yusup Ramathoni; Sudiyono; Ahmad Rizqi (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
The digital era has brought numerous positive impacts that significantly transform various aspects of human life. Information and communication technology, particularly the internet and social media, has opened up boundless spaces that enable freedom of expression, interaction, and the rapid and widespread dissemination of information. However, this digital transformation does not only bring positive effects. On the other hand, the digital sphere also presents new risks, such as the spread of false information (hoaxes), hate speech, cyberbullying, pornography, as well as cybercrimes such as fraud and hacking. Crimes committed in cyberspace are often more complex as they transcend national jurisdictions, are difficult to trace, and have wide-ranging impacts on public security and order. At the same time, its enforcement potentially restricts freedom of expression, which is a pillar of democracy. This tension between legal protection and freedom of expression raises the question: How have the development and dynamics of legal protection and the threats to freedom of expression under the Electronic Information and Transactions Law (ITE Law) evolved? This study aims to understand, analyze, and interpret the norms by employing a juridical-normative research approach, given the issues being addressed. Fundamentally, the ITE Law carries a noble purpose: to provide legal certainty, protect society from cybercrimes, and create a safe and healthy digital ecosystem. However, in practice, the implementation of the ITE Law is not free from problems. Several provisions, particularly those concerning defamation and hate speech, often spark controversy as they are considered to restrict freedom of expression.